2008
DOI: 10.1002/adfm.200700926
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Organic Molecules with Inorganic Nanoparticles: Hybrid Nanodiodes

Abstract: A monolayer of inorganic nanoparticles and a monolayer of organic molecules have been electrostatically assembled in sequence. Such assemblies or organizations exhibit electrical rectification. When the sequence of the organization is reversed, the direction of rectification becomes opposite. In both n‐type ZnO/organic and organic/n‐ZnO assemblies, electron flow is favorable from the n‐ZnO nanoparticle to the (electron‐accepting) organic molecule. While the individual components do not show any rectification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This improved response and electrical measurement as seen in Figure point to the significant role of surface and interfaces formed between CuO and SnO 2 . Similar role of interfaces has been discussed in literatures . They modulate electronic states and influence physiochemical properties.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This improved response and electrical measurement as seen in Figure point to the significant role of surface and interfaces formed between CuO and SnO 2 . Similar role of interfaces has been discussed in literatures . They modulate electronic states and influence physiochemical properties.…”
Section: Resultssupporting
confidence: 71%
“…Similar role of interfaces has been discussed in literatures. [34,35] They modulate electronic states and influence physiochemical properties. In general, individual n-p junction creates a depletion layer which is in excess of chemisorbed based depletion in SnO 2 .…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…Theoretical approaches based on the equation of motion method [100] or Fock space formalism [101] have also begun to be appear to gain understanding of this regime. Although, we have discussed mainly about one of the technologically useful non-linear phenomena, namely, Negative differential resistance, other phenomena such as multistability and hysteresis, which arise out of structural changes in a molecule during transport together with inelastic processes due to interactions at different energy and length scales in organic, inorganic or hybrid systems still remain the subjects of active current research [102,103,104,105].…”
Section: Discussionmentioning
confidence: 99%
“…In order to remove the dyes from the aqueous environment, various methods have been explored, such as photocatalysis, adsorption, electrochemical degradation, acidication, etc. In order to overcome these drawbacks, efforts have been made via combination ZnO with other components including inorganic or organic semiconductor, noble metals, and grapheme et al [11][12][13][14] Owing to the appropriate redox properties for the sensitization of large band-gap semiconductors and the thermal stability, metal phthalocyanine (MPc) have received signicant attention for advanced applications in dye-sensitized solar cells, gas sensors and molecular electronic devices. [2][3][4] As an important wide and direct band-gap semiconductor, ZnO has been deemed to be an efficient photocatalyst because of its high catalytic efficiency, low cost, and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The rapid recombination of photogenerated electron-hole pairs formed in photocatalytic processes is also a major obstacle for increasing the photocatalytic efficiency of ZnO. In order to overcome these drawbacks, efforts have been made via combination ZnO with other components including inorganic or organic semiconductor, noble metals, and grapheme et al [11][12][13][14] Owing to the appropriate redox properties for the sensitization of large band-gap semiconductors and the thermal stability, metal phthalocyanine (MPc) have received signicant attention for advanced applications in dye-sensitized solar cells, gas sensors and molecular electronic devices. [15][16][17][18][19][20] More recently, it has been demonstrated that MPc could hinder the charge recombination and improve the photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%